Respuesta :

Answer:

[tex]P=775[/tex]

Step-by-step explanation:

The Simple Interest Equation is [tex]A = P(1 + rt)[/tex]

where

A = Total Accrued Amount (principal + interest)

P = Principal Amount

I = Interest Amount

t = Time Period involved in months or years

In this case, we do not know the values ​​of the equation (A and P), but we know the amount of interest accrued

If we define our principal whit this formula, we are able to know the rest of the values:

[tex]A-P= interest[/tex]

clearing

[tex]A=interest+P[/tex]

replacing

[tex]426.25 + P = P (1+(0.11(5))[/tex]

Solving

[tex]426.25+P=1.55P[/tex]

[tex]P-1.55P=-426.25[/tex]

[tex]-0.55P=-426.65[/tex]

[tex]P=\frac{-426.25}{-0.55}[/tex]

[tex]P=775[/tex]

ACCESS MORE